Thermal alteration of CM carbonaceous chondrites: Mineralogical changes and metamorphic temperatures. (1st April 2021) - King, A.J.; Schofield, P.F.; Russell, S.S.
Abstract: The CM carbonaceous chondrite meteorites provide a record of low temperature (<150 °C) aqueous reactions in the early solar system. A number of CM chondrites also experienced short-lived, post-hydration thermal metamorphism at temperatures of ∼200 °C to >750 °C. The exact conditions of thermal metamorphism and the relationship between the unheated and heated CM chondrites are not well constrained but are crucial to understanding the formation and evolution of hydrous asteroids. Here we have used position-sensitive-detector X-ray diffraction (PSD-XRD), thermogravimetric analysis (TGA) and transmission infrared (IR) spectroscopy to characterise the mineralogy and water contents of 14 heated CM and ungrouped carbonaceous chondrites. We show that heated CM chondrites underwent the same degree of aqueous alteration as the unheated CMs, however upon thermal metamorphism their mineralogy initially (300–500 °C) changed from hydrated phyllosilicates to a dehydrated amorphous phyllosilicate phase. At higher temperatures (>500 °C) we observe recrystallisation of olivine and Fe-sulphides and the formation of metal. Thermal metamorphism also caused the water contents of heated CM chondrites to decrease from ∼13 wt% to ∼3 wt% and a subsequent reduction in the intensity of the 3 μm feature in IR spectra. We estimate that the heated CM chondrites have lost ∼15 - >65% of the water they contained at the end of aqueous alteration. If impacts were the main cause of metamorphism, this is consistent with shock pressures of ∼20–50 GPa. However, not all heated CM chondrites retain shock features suggesting that some were instead heated by solar radiation. Evidence from the Hayabusa2 and ORSIRS-REx missions suggest that dehydrated materials may be common on the surfaces of primitive asteroids and our results will support upcoming analysis of samples returned from asteroids Ryugu and Bennu.